Media Pembelajaran Video Animasi Biomekanika Melalui Metode Circuit Training untuk Meningkatkan Keterampilan Dasar Volleyball - Susila, Linda; Hidayat, Taufiq; Shohibul, Shohibul; Rizky, Rizky (Jurnal Porkes, 2024)
This study aims to produce learning media based on animated video applications through the circuit training method to improve basic volleyball skills. This research is a development (Research & Development) that refers to Thiangarajan's 4-D (Four-D) device development model. define, design, develop, disseminate. The stages of this model include define, design, develop and disseminate at the product validation stage through review by experts and product trials to students. The data collection instrument used was a questionnaire. The results of this study are the process of developing biomechanical animation media and the feasibility of animated videos obtained based on the average of each validator. Data analysis of volleyball skills test content/material expert review reached 90% very good. Biomechanics animation media expert review 91% good, media review reached 93% good, small group validation reached 93% good and large group validation reached 94 very good. It is concluded that in this learning design, using the R&D model, define, design, develop, disseminte, a biomechanical animated video learning media has been produced through the circuit training method.